Transcriptomic insights into adenoid cystic carcinoma via RNA sequencing - Tang, Yu-Fang; An, Pu-Gen; Gu, Bao-Xin; Yi, Shu; Hu, Xiao; Wu, Wen-Jie; Zhang, Jie (Frontiers in Genetics, 2023)
Background: The aim of this study was to investigate the underlying mechanisms of adenoid cystic carcinoma of the salivary gland (SACC) at the transcriptome level. Materials & Methods: We obtained paired tumor and normal salivary gland tissues from 15 SACC patients, which were prepared for RNA sequencing. Results: Gene enrichment analysis revealed that the upregulated pathways were mainly involved in axonogenesis, and the downregulated pathways were mainly related to leukocyte migration, the adaptive immune response, lymphocyte-mediated immunity, and the humoral immune response. T cells, B cells and NK cells showed low infiltration in SACC tissues. In addition to the gene fusions MYB-NFIB and MYBL1-NFIB, a new gene fusion, TVP23C-CDRT4, was also detected in 3 SACC tissues. PRAME was significantly upregulated in SACC tissues, while antigen-presenting human leukocyte antigen (HLA) genes were downregulated. Conclusion: We found a new gene fusion, TVP23C-CDRT4, that was highly expressed in SACC. PRAME may be an attractive target for SACC immunotherapy.